Perception and performance in a flipped financial mathematics classroom - Lopes, Ana Paula (2018)
The “flipped” classroom model is a new organizational design for the teaching and learning paradigm, as its name transmits, stands for the pedagogical switch of the traditional academic procedure as students’ first contact with the subjects is made outside the “four-wall classroom bounds”. Teachers’ role is transposed into a kind of guide and facilitator, indicating the way to go, avoiding to walk in a parallel path, or even ahead, but indicating the way to go, motivating students in their own knowledge construction, letting them lead the way, following and supporting, constantly and carefully monitoring their learning outcomes. Classroom time is consumed with open discussions, solving tasks and application problems, clarifying the supporting fundaments, in order to improve students’ engagement into their learning process in a collaborative environment. A flipped model was implemented into a Financial Mathematics Course at ISCAP and the sample of our study consisted of 803 students, enrolled in 2014, 2015 and 2016. The main purpose of this paper is to investigate how the incorporation of the flipped classroom model into a Financial Mathematics class, affected students’ class training, learning, and achievement. The results obtained with this approach have shown a positive impact on students’ achievement overall.